EFFECT OF AGE AND PARITY ON PREGNANT WOMEN'S KNOWLEDGE ABOUT DISCOMFORT OF THE THIRD TRIMESTER - Maryati, Sri; Yanti, Damai (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Pregnancy is a physiological process that almost always takes place in every woman. However, there are some mothers who experience discomfort. Knowledge can be influenced by a person's characteristics including age and parity. Increasing a person's age can affect the increase in knowledge gained. Likewise, mothers who have several children generally have better knowledge because they have had hands-on experience in previous pregnancies. The incidence of discomfort in the third trimester at Clinic A was 56 cases. The purpose of this study was to determine the effect of age and parity on knowledge of pregnant women about discomfort of the third trimester at Kilink "A" Banjaran in 2022. Method. This research is an analytic study with a cross sectional approach. The sample in this study were 85 pregnant women in the third trimester. Data analysis used multivariate analysis with linear regression, namely to test jointly the effect of the dependent variable, namely age and parity with the independent variable, namely knowledge. Result & Analysis. The results showed that the age variable has a correlation value of 0.363 while the parity variable has a correlation value of 0.041, meaning that the age factor is the most influential factor on knowledge. This can be related to the theory that the older a person is, the experience will increase and affect knowledge. this can happen because in this study most of the mothers were aged 25-35 years. Discussion. The age of 20-35 years is a mature age and has sufficient knowledge and experience both in terms of maturity in thinking and mentally to live a household.